Sex difference in the association between blood alcohol concentration and serum ferritin - Yehia, Asmaa; Sousa, Ricardo A. L.; Abulseoud, Osama A. (Frontiers in Psychiatry, 2023)
The sex difference in alcohol use disorder (AUD) is ingrained in distinctive neurobiological responses between men and women, which necessitates further investigation for a more tailored management.Minding the findings of iron dysregulation in AUD and the sex difference in iron homeostasis in multiple physiological and pathological settings, Wwe examined the sex difference in the association between serum ferritin and blood alcohol concentration (BAC) in intoxicated males (n=125) and females (n=59).We included patients with both serum ferritin tested of any value and a BAC above the level of detection during the same hospital admission period. We investigated sex difference in the relationship between BAC, serum ferritin and liver enzymes in intoxicated critically ill and non-critically ill patients. We found a negative association between serum ferritin and BAC in critically ill, intoxicated females (R 2 = 0.44, F(1, 14) = 11.02, P=0.005), with much attenuated serum ferritin in females compared to their male counterparts (194.5±280.4 vs. 806.3±3405.7 ng/L, P=0.002). We found a positive association between serum ferritin and liver enzymes (Alanine transaminase (ALT) and aspartate transferase (AST)) in critically ill intoxicated females (ALT: R 2 = 0.48, F(1, 10)=9.1, P=0.013) (AST: R 2 = 0.68, F(1, 10)=21.2, P=0.001) and in non-critically ill intoxicated males (ALT: R 2 = 0.1, F(1, 83)=9.4, P=0.003) (AST: R 2 = 0.1, F(1, 78)=10.5, P=0.002). The effect of BAC on serum ferritin was not mediated by ALT (Indirect effect: (B=0.13, P=0.1)).We also found a significant effect of sex, anemia, intensive care unit (ICU) admission and mortality on serum ferritin. Our results suggest that high BAC in intoxicated female patients is associated with attenuated serum ferritin levels, questioning the role of low serum ferritin in female vulnerability to alcohol.